Virtual Three-Dimensional Magnetic Resonance Fetal Cystoscopy: A Novel Modality for Precise in Utero Evaluation of Urinary Tract - Kajbafzadeh, Abdol-Mohammad; Nabavizadeh, Behnam; Seyed Hossein Beigi, Reza; Alinia, Pariya; Mirshahvalad, Seyed Ali (Urology Journal, 2020)
Urogenital anomalies are the most prevalent anomalies detected during pregnancy. Timely detection of these conditions could facilitate proper post-natal management and improve outcomes. In some cases, precise delineation of fetal urinary tract utilizing ultrasonography is not feasible. Moreover, sometimes the ultrasound study is technically limited. Magnetic resonance imaging could clarify the diagnosis in these situations. Prenatal ultrasonography indicated hydronephrosis and a 14 mm cystic lesion at right ureterovesical junction in a 25-week fetus. However, fetal magnetic resonance urography was not able to precisely clarify the condition and extension of ureterocele into the urethra. Fetal magnetic resonance virtual cystoscopy clearly demonstrated anatomy and extension of ureterocele. This modality provides three-dimensional cystoscopic-like view of urinary bladder and facilitates postnatal management.